Using chatbots to scaffold EFL students’ argumentative writing - Guo, Kai; Wang, Jian; Chu, Samuel Kai Wah (Assessing writing, 2022)
Research suggests that English as a foreign language (EFL) students’ argumentative writing benefits from interactions with peers. However, finding an ideal partner to interact with can be difficult in practice, and chatbots have been suggested as a potential solution to this problem. Chatbots are a form of artificial intelligence (AI) designed to engage in turn-by-turn conversations with human users. In this paper, we propose a chatbot-assisted approach to the teaching and learning of argumentative writing. We describe Argumate, a novel chatbot system that we developed to scaffold students’ argument construction, and we discuss the advantages and limitations of using this system to assist students in producing high-quality argumentative writing. •Integration of artificial intelligence (AI) chatbots into writing classrooms.•Proposal of a chatbot-assisted approach to argumentative writing.•Design and development of a chatbot system named Argumate.•Argumate can help with students’ idea generation and counterargument integration.